The Safety of Infliximab Infusions in the Community Setting - James Ducharme; Cindy Pelletier; Ramesh Zacharias (Canadian Journal of Gastroenterology)
BACKGROUND: Tumour necrosis factor-alpha (TNFα) has an important role in the pathogenesis of inflammatory conditions such as rheumatoid arthritis, Crohn’s disease, ulcerative colitis and psoriasis. Infliximab, a chimeric anti-TNFα monoclonal antibody, has been shown to reduce the severity of symptoms or induces remission of active disease. Infusions have generally been limited to the hospital setting due to cost and concerns for patient safety. Studies defining its efficacy and safety have, therefore, originated almost exclusively from hospital settings.